Synthesis and Characterization of Activated Carbon Coated Alumina as Nano Adsorbent. (2017) - Sree Harsha, K.R.; Murthy, M.; Udayasimha, L.; Dharmaprakash; Rangappa, Dinesh
Abstract: High surface area of Activated carbon and Nano alumina have attracted researchers in Environmental remediation application as nano adsorbents for removal of heavy metal ions from the industrial waste water. Activated carbon is coated on Alumina by hydrothermal method at relatively low temperature of 120°C. In our present work, we have synthesised nano alumina coated activated Carbon as adsorbent for heavy metal removal application. Activated carbon coated Alumina is characterised by X-ray Diffractometer (XRD), Scanning Electron microscope (SEM), Energy Dispersive Spectroscopy (EDX), Fourier Transform Infrared Spectroscopy (FTIR). The obtained XRD results confirmed the formation of corundum phase alumina with well crystallinity with an average particle size of about 50 nm as calculated by Debey Scherer's equation. The SEM image confirmed the carbon particles coated with alumina nanoparticles, FTIR shows the presence of Al-O stretching vibrations below 600 cm -1, EDX confirms the presence of all Al, O and Carbon Elements Showing purity of the sample, activated carbon coated Nano Alumina was used as adsorbent for removal of heavy metals. Batch mode adsorption was carried out by varying the contact time of adsorbent. The results showed excellent removal of Ni(II) and Cu(II) ions.